2019
DOI: 10.1002/biot.201800493
|View full text |Cite
|
Sign up to set email alerts
|

The Construction of an In Vitro Synthetic Enzymatic Biosystem that Facilitates Laminaribiose Biosynthesis from Maltodextrin and Glucose

Abstract: Laminaribiose is a reducing disaccharide linked by a β‐1,3 glycosidic bond; it is also a precursor for building blocks in the pharmaceutical industry, a powerful germinating agent and antiseptic, as well as a potential prebiotic. In this study, an in vitro enzymatic biosystem composed of α‐glucan phosphorylase, laminaribiose phosphorylase, isoamylase, and 4‐glucanotransferase is designed for the one‐pot synthesis of laminaribiose from low‐cost maltodextrin and glucose. Through condition optimization, 51 mM lam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 39 publications
0
21
0
Order By: Relevance
“…Orthogonal two‐enzyme phosphorylase cascades have been reported for the synthesis of disaccharides (e.g., cellobiose, α,α‐trehalose, laminaribiose, kojibiose, nigerose), oligo‐, and polysaccharides (e.g., β‐glucans, amylose). Sucrose or starch was the donor substrate to fuel the phosphate/αGlc 1‐ P shuttle .…”
Section: Introductionmentioning
confidence: 99%
“…Orthogonal two‐enzyme phosphorylase cascades have been reported for the synthesis of disaccharides (e.g., cellobiose, α,α‐trehalose, laminaribiose, kojibiose, nigerose), oligo‐, and polysaccharides (e.g., β‐glucans, amylose). Sucrose or starch was the donor substrate to fuel the phosphate/αGlc 1‐ P shuttle .…”
Section: Introductionmentioning
confidence: 99%
“…These data indicated that Mdc had the ability to catalyze OAA to MSA and the specific activity achieved 9.37 μmol/min/g ( Figure 2D ). In vitro multi-enzyme system has emerged as a promising bio-manufacturing platform for producing desired products ( Sun et al, 2019 ). The artificial biosynthetic pathway, including only two enzymes, may be feasible to produce malonic acid in vitro in the future.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the rational and semiquantitative principle of promoter and RBS strength (strong/medium/weak) used in plasmid construction, we believe that the results of this study have excellent replication potential when applied to other enzyme cascades in different fields of bio-catalysis. Besides the well-known oxidoreductase systems that require regeneration of nicotinamide coenzymes and/or flavin cofactors, [1][2][3][4][5]9,10,20] two-enzyme cascades of glycoside phosphorylases similar to the one used here, [67][68][69] or cascades of two nucleoside phosphorylases, [21,22,70] are gaining increased importance. Two-enzyme cascades involving sugar nucleotide-dependent glycosyltransferases are emerging systems for synthesis.…”
Section: Resultsmentioning
confidence: 99%